Blinders, blunders, and wars : what America and China can learn - Gompert, David C.; Binnendijk, Hans; Lin, Bonny (RAND, 2014)
The history of wars caused by misjudgments, from Napoleon's invasion of Russia to America's invasion of Iraq, reveals that leaders relied on cognitive models, or simplified representations of their worlds, that were seriously at odds with objective reality. Blinders, Blunders, and Wars analyzes eight historical examples of strategic blunders regarding war and peace and four examples of decisions that turned out well, and then applies those lessons to the current Sino-American case. Leaders' egos, intuitions, unwarranted self-confidence, and aversion to information that contradicted their views prevented them from correcting their models. Yet advisors and bureaucracies can be inadequate safeguards and can, out of fawning or fear, reinforce leaders' flawed thinking. War between China and the United States is more likely to occur by blunder than from rational premeditation. Yet flawed Chinese and American cognitive models of one another are creating strategic distrust, which could increase the danger of misjudgment by either or both, the likelihood of crises, and the possibility of war. Although these American and Chinese leaders have unprecedented access to information, there is no guarantee they will use it well when faced with choices concerning war and peace. They can learn from Blinders, Blunders, and Wars. As a general remedy, the authors recommend the establishment of a government body providing independent analysis and advice on war-and-peace decisions by critiquing information use, assumptions, assessments, reasoning, options, and plans. For the Sino-U.S. case, they offer a set of measures to bring the models each has of the other into line with objective reality.